A2 to b Renal Transplantation: One Center's Experience and the Implications for Decreasing Wait Times and Reducing Racial Disparities in Organ Allocation. (July 2018) - Shapiro, Ron; Van Kluyve, Nicole; Khaim, Rafael; Geatrakas, Sara
Abstract : Purpose: The longest wait times for deceased donor renal transplantation are for B blood group recipients, a group largely composed of ethnic minorities. Previous studies have shown excellent outcomes with kidney transplantation from A2 donors in recipients with low pre-transplant anti-A titers. Few studies have specifically evaluated the implication for wait times, early outcomes, and ethnic disparities in organ allocation. Methods: A single center retrospective chart review of all recipients of A2 to B living or deceased donor kidney transplants between November 2014 and December 2017 was performed. The records of 20 adults were identified. Eligible recipients had anti-A IgG titers ⩽ 1:8. Serum creatinine levels were assessed at discharge, three months, one year, and at most recent follow up post-transplant. Wait times were compared with our center, local, and regional wait times. Ethnicity of recipients was compared. Results: Over a period of 37 months, 20 A2 to B kidney transplants were performed, 19 from deceased donors and one from a living donor. One graft had primary non-function and one failed two years post transplantation due to disease recurrence. The incidence of hyperacute rejection or thrombotic microangiopathy was zero percent. Four (20%) had delayed graft function; all resolved within three months. Eighteen patients were non-white, ethnic minorities. Average wait time was 7.5 years from the time of dialysis initiation and 3.4 years from the time of listing (for the deceased donor recipients), compared with our average center B blood type wait time of 11.4 years. The mean creatinine at discharge was 2.8 mg/dL, 1.4 at three months, and 1.2 at most recent follow up. Other observations included a median hospitalization of six days, mean donor KDPI of 45%, mean donor age of 45; mean cold ischemic time was 15 hours. Conclusion: Our data confirm previous reports that A2 to B kidney transplantation does not adversely affect graft or patient survival. A2 to B kidney transplantation is a viable option for transplant centers to reduce the longest wait times for B blood group recipients. This practice addresses waiting time disparities for the B blood group population as well as for ethnic minorities.